2017
DOI: 10.1111/tid.12761
|View full text |Cite
|
Sign up to set email alerts
|

Absence of JC polyomavirus (JCPyV) viremia in early post‐transplant JCPyV nephropathy: A case report

Abstract: JC polyomavirus (JCPyV)-associated nephropathy (JCPyVAN) occurs in <3% of PVAN cases after renal transplantation. We report the first confirmed case to our knowledge of JCPyVAN diagnosed by kidney biopsy in the early 6 months post transplant in Thailand. In this case report, recovery of renal allograft function was not observed after reduction of immunosuppressive agents and administration of intravenous immunoglobulin and cidofovir. Despite persistent JCPyV viruria, no significant further decline in allograft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Among HIV-infected patients with PML, JCPyV viremia is not more frequent than in matched HIV-infected control patients (83). Among the few studies regarding JCPyVAN, JCPyV viremia was reported in some patients with low viral loads of approximately 1E3 copies/ml and transient viremia, contrasting with the high viral loads (Ͼ1E6 copies/ml) in urine samples (88,91,92). (b) Detection in blood samples of nontransplanted individuals.…”
Section: Dna Viruses Double-stranded Dna Virusesmentioning
confidence: 99%
“…Among HIV-infected patients with PML, JCPyV viremia is not more frequent than in matched HIV-infected control patients (83). Among the few studies regarding JCPyVAN, JCPyV viremia was reported in some patients with low viral loads of approximately 1E3 copies/ml and transient viremia, contrasting with the high viral loads (Ͼ1E6 copies/ml) in urine samples (88,91,92). (b) Detection in blood samples of nontransplanted individuals.…”
Section: Dna Viruses Double-stranded Dna Virusesmentioning
confidence: 99%
“…5,6 Biopsy-proven JC-PVN, on the other hand, is quite rare, with only a handful of reported cases. [7][8][9][10][11][12][13][14][15][16] To date, the only extensive study on JC-PVN by Drachenberg et al reported an incidence of 0.9%, which constituted 6 biopsy-proven cases. 7 In comparison, BK-PVN for this same study had an incidence of 5.5%, >6 times that of JC-PVN.…”
Section: Introductionmentioning
confidence: 99%
“…Not only is the kidney a major site of persistent JCPyV infection, but it is also a source of graft failure in kidney transplant patients. Case reports have demonstrated that, while rare, transplant patients can experience JCPyV-associated nephropathy (JC-PVAN) [ 90 , 91 , 92 , 93 , 94 , 95 ]. The mechanism behind how JCPyV infiltrates the kidney and how JC-PVAN may develop is unknown.…”
Section: How Is Jcpyv Transmitted?mentioning
confidence: 99%